Multi-dimensional Optimal Order Detection (MOOD) : a very high-order finite volume scheme for conservation laws on unstructured meshes - Clain, Stéphane (2011)
The Multi-dimensional Optimal Order Detection (MOOD) method is an original Very High-Order Finite Volume (FV) method for conservation laws on unstructured meshes. The method is based on an a posteriori degree reduction of local polynomial reconstructions on cells where prescribed stability conditions are not fulfilled. Numerical experiments on advection and Euler equations problems are drawn to prove the efficiency and competitiveness of the MOOD method.